GENDERED LEARNING BIOGRAPHIES: BECOMING A TEACHER IN MULTICULTURAL EDUCATION - Mazeikiene, Natalija; Gerulaitiene, Egle (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Research presented in the paper focuses on learning biographies and professional identity development of 14 female and male teachers at university colleges in Norway. Biographical narratives reveal subjective accounts and perception of gender roles and it exposes interaction of formal, non-formal, informal experiential learning in different cultural contexts (journeys), combination of learning, work and family life. Learning as a lifelong process is inter-woven with distribution of power in society, social stratification, structural economic and labour market processes, social identities (including gender) and relation between various spheres of social life (public and private, work, family and learning, etc.). In the settings of late modernity globalisation and the process of disembedding mechanisms of social institutions allow individuals to experience new cultures, new lifestyles and feel disembedded and detached from institutions. Internationalization of higher education is an example of empowering detachment mechanisms, when people choose to learn in different cultural settings and develop intercultural competence through experiential learning. The aim of the paper is to analyse (re)construction of self-identity in biographical narratives and conceptualize male and female learning biographies and learning paths in becoming teachers in multicultural education.